The influence of organizational culture toward 5S’s practices: A case of Universiti Utara Malaysia - Hashim, Norhazira Nazwa; Radzuan, Kamaruddin (Universiti Utara Malaysia, 2020)
This research aimed to identify the influence of organizational culture towards 5s practice. The four organizational cultures are involvement, consistency, adaptability and mission as independent variables, while the 5s practices is a dependent variable. This study aimed to identify the relationship between organizational culture towards 5s practices in. This study chosen 59 respondents as a sample size based from on the population of STML staff. The questionnaire will give to 59 respondents in STML. The method that is used is quantitative and question is based on five scales Likert such as 1 (strongly disagreed) to 5 (strongly agreed). The finding shows that culture of involvement to be significant elements of organizational culture towards 5s practice. The organizational culture towards 5s practices did play an effective role in influencing the organizational performance in department productivity.